2008
DOI: 10.1210/jc.2007-1633
|View full text |Cite
|
Sign up to set email alerts
|

Low Circulating Insulin-Like Growth Factor I Bioactivity in Elderly Men Is Associated with Increased Mortality

Abstract: Our study suggests that a relatively high circulating IGF-I bioactivity in elderly men is associated with extended survival and with reduced cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 28 publications
1
64
2
4
Order By: Relevance
“…We measured total serum IGF1 as an accepted measure of IGF1 status. A recently reported bioassay based on activation of the IGF1-specific kinase receptor may provide a means of assessing circulating bioactive IGF1 (47), but this method is not in general use at this moment. Furthermore, biological effects and bioavailability of IGF1 are modulated through IGFBPs, which control IGF1 access to cell surface receptors (1).…”
Section: Discussionmentioning
confidence: 99%
“…We measured total serum IGF1 as an accepted measure of IGF1 status. A recently reported bioassay based on activation of the IGF1-specific kinase receptor may provide a means of assessing circulating bioactive IGF1 (47), but this method is not in general use at this moment. Furthermore, biological effects and bioavailability of IGF1 are modulated through IGFBPs, which control IGF1 access to cell surface receptors (1).…”
Section: Discussionmentioning
confidence: 99%
“…bioactive IGF1) (21). Subsequent studies have demonstrated that bioactive IGF1 is inversely correlated with age (22), significantly higher in females compared with males (23), and positively correlated with IGF1 as measured by immunoassay (i.e. total IGF1).…”
Section: Introductionmentioning
confidence: 98%
“…In several studies, lower IGF1 levels have also been associated with all-cause or CVD-related mortality (19,20,21). AAA and atherosclerotic CVD share common risk factors such as smoking and elevated blood pressure or cholesterol levels, and often co-exist.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore a 'healthy survivor' effect is possible which would make our results more conservative and applicable to generally healthier community-dwelling older men, and we cannot comment on associations in women. We did not have the capacity to measure free or unbound IGF1 levels either by immunoassay or ultracentrifugation, nor were we able to measure circulating IGF1 bioactivity (20). Therefore, our assessment was limited to circulating total IGF1, IGFBP1 and IGFBP3.…”
Section: Discussionmentioning
confidence: 99%